From Lawn to Health: Understanding the Prostate Cancer Risk in Light DIY Activities - Rui Yang; Xiguang Zhang; Chen Chen; Ya Li; Jun Yin (American Journal of Men's Health)
This study employs two-sample Mendelian Randomization (MR) analysis to investigate the causal relationship between light DIY activities and prostate cancer. We used single nucleotide polymorphisms (SNPs) associated with light DIY activities obtained from published genome-wide association studies (GWASs) and summary-level genetic data related to prostate cancer from published GWAS. The primary analysis was conducted using the inverse-variance weighted (IVW) method for two-sample MR analysis. Cochran’s Q statistic was used to assess heterogeneity, MR-Egger was employed to detect horizontal pleiotropy, and “leave-one-out” analysis was performed for sensitivity analysis. Given the presence of heterogeneity, the random-effects IVW method was used for the primary analysis. The random-effects IVW results indicated a positive causal relationship between participation in light DIY activities and the risk of prostate cancer (odds ratio [OR] = 1.024, 95% confidence interval [CI]: 1.001–1.048; p = .039). The weighted median (WM) method results supported this finding (OR = 1.025, 95% CI: 1.003–1.048; p = .024). Participation in light DIY activities may slightly increase the risk of prostate cancer. This finding emphasizes the need to carefully consider the types and intensities of physical activities when making public health recommendations and personal lifestyle choices.